Odpowiedzi

2010-03-22T16:14:29+01:00
-8z+5= -2-1
-8z=-2-1-5
-8z=-8
z=1

-2m+7=m-6
-2m-m=-6-7
-3m=-13
m=4 1/13

6-5x=2-7
-5x=2-7-6
-5x=-11
x=2,2

5t+1=8-6t
5t+6t=8-1
11t=7
t= 1 4/7
Najlepsza Odpowiedź!
2010-03-22T16:16:03+01:00
-8z+5=-2-1
-8z=-2-1-5
-8z=-8 /: (-8)
z=1

-2m+7=m-6
-2m-m=-6-7
-3m=-13 /: (-3)
m=13/3
m= 4 i jedna trzecia

6-5x=2-7
-5x=2-7-6
-5x=-11 /: (-5)
x= 11/5
x= 2 i jedna piąta

5t+1=8-6t
5t+6t=8-1
11t=7 /: 11
t=7/11
2010-03-22T16:16:34+01:00
-8z+5= -2-1
-8z = -2-1-5
-8z = -8 /:(-8)
z = 1

-2m+7=m-6
-2m = m-6 -7
-2m -m = -13
-3m = -13/:(-3)
m = 13/3
m =4 i 1/3

6-5x=2-7
-5x = 2-7-6
-5x = -11/: (-5)
x = 11/5
x = 2 i 1/5

5t+1=8-6t
5t + 6t = 8 - 1
11t = 7 / : 11
t = 7/11